(untitled) (Scientific journal of the Fergana State University, 2025)
This article presents the results of a study of the alkaloid composition of Liridendron tulipifera L. The composition of Liridendron tulipifera L was studied using UV, IR, and mass spectrometry. The structures of the identified alkaloids were confirmed using the above methods.